Concurrent beneficial (vitamin D production) and hazardous (cutaneous DNA damage) impact of repeated low‐level summer sunlight exposures. (1st December 2016) - Felton, S.J.; Cooke, M.S.; Kift, R.; Berry, J.L.; Webb, A.R.; Lam, P.M.W.; de Gruijl, F.R.; Vail, A.; Rhodes, L.E.
Summary: Background: The concurrent impact of repeated low‐level summer sunlight exposures on vitamin D production and cutaneous DNA damage, potentially leading to mutagenesis and skin cancer, is unknown. Objectives: This is an experimental study (i) to determine the dual impact of repeated low‐level sunlight exposures on vitamin D status and DNA damage/repair (via both skin and urinary biomarkers) in light‐skinned adults; and (ii) to compare outcomes following the same exposures in brown‐skinned adults. Methods: Ten white (phototype II) and six South Asian volunteers (phototype V), aged 23–59 years, received 6 weeks' simulated summer sunlight exposures (95% ultraviolet A/5% ultraviolet B, 1·3 standard erythemal doses three times weekly) wearing summer clothing exposing ~35% body surface area. Assessments made were circulating 25‐hydroxyvitamin D [25(OH)D], immunohistochemistry for cyclobutane pyrimidine dimer (CPD)‐positive nuclei and urinary biomarkers of direct and oxidative (8‐oxo‐deoxyguanosine) DNA damage. Results: Serum 25(OH)D rose from mean 36·5 ± 13·0 to 54·3 ± 10·5 nmol L −1 (14·6 ± 5·2 to 21·7 ± 4·2 ng mL −1 ) in phototype II vs. 17·2 ± 6·3 to 25·5 ± 9·5 nmol L −1 (6·9 ± 2·5 to 10·2 ± 3·8 ng mL −1 ) in phototype V ( P < 0·05). Phototype II skin showed CPD‐positive nuclei immediately postcourse, mean 44% (range 27–84) cleared after 24 h, contrasting with minimal DNA damage and full clearance in phototype V ( P < 0·001). The findings did not differ from those following single ultraviolet radiation (UVR) exposure. Urinary CPDs remained below the detection threshold in both groups; 8‐oxo‐deoxyguanosine was higher in phototype II than V ( P = 0·002), but was unaffected by UVR. Conclusions: Low‐dose summer sunlight exposures confer vitamin D sufficiency in light‐skinned people concurrently with low‐level, nonaccumulating DNA damage. The same exposures produce minimal DNA damage but less vitamin D in brown‐skinned people. This informs tailoring of sun‐exposure policies.